Vítimas invisíveis: o pânico moral acerca do tráfico de pessoas para exploração sexual por uma perspectiva de gênero - Cunha, Juliana Frei [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to examine human trafficking for sexual exploitation by an optical counter-hegemonic and gender, in other words, depreciating crime's seriousness through revaluation of macrosociological contexts in which trafficking is inserted, as well as human rights, claims of victims and alleged victims. By locating human trafficking for sexual exploitation in the symbiosis between patriarchal-capitalist, promoted by the dynamics of globalization, crime is seen as a structural consequence. The criminal policy of confrontation lacks a new approach. In this sense, guided by critical theoretical framework, it is analyzed the ramifications of human trafficking in the scope of criminal science and evidences of an alternative policy are outlined. Due to socio-cultural constructs, society does not openly deals with issues related to sexuality, which assists in creating a sex panic about sexual exploitation. Therefore, it is searched other exploratory purposes of trafficking. Revealing hidden interests such as immigration control and the moral crusade against prostitution. From this point, you can understand the construction of a moral panic about the phenomenon of human trafficking for sexual exploitation and reproduction of these ideas. Considering this issue and the persistence of these phenomenon, theories of recognition to identify vulnerabilities and differences in social groups are used. Despite an alternative criminal policy, criminal law is far from being an effective tool to reduce the incidence of this crime or prevent it, protection and recognition of victims's claims and other affected segments. It is proposed, therefore, the improvement of public policies to promote parity levels of social participation among various segments: undocumented immigrants, sex workers and victims. Specifically the trafficking of people for sexual exploitation, it is argued the need for recognition and regulation of labor of sex workers...

Esta pesquisa visa analisar o tráfico de pessoas para a exploração sexual por uma óptica contra-hegemônica e de gênero, ou seja, desvalorizando a aparência deste crime por meio da revalorização dos contextos macrossociológicos, nos quais o tráfico está inserido, assim como dos direitos humanos, das demandas das vítimas e supostas vítimas. Ao localizar o tráfico de pessoas para exploração sexual na simbiose entre patriarcado-capitalismo, fomentado pelas dinâmicas da globalização, vislumbra-se o crime como uma consequência estrutural. A política criminal de enfrentamento carece de alterações. Neste sentido, pautado por referenciais teóricos críticos analisa-se os desdobramentos do tráfico de pessoas na seara das ciências criminais e delineiam-se indícios de uma política alternativa. Devido a constructos socioculturais, a sociedade não trata abertamente de assuntos referentes à sexualidade, o que auxilia na criação de um pânico sexual acerca da exploração sexual. Busca-se, portanto, apresentar as outras finalidades do tráfico de pessoas e revelar interesses ocultos como o controle migratório e a cruzada moral contra a prostituição. A partir deste ponto, é possível compreender a construção de um pânico moral acerca do fenômeno do tráfico de pessoas para a exploração sexual e a reprodução destas ideias. Considerando esta problemática e a persistência do fenômeno, recorre-se às teorias do reconhecimento para identificar as vulnerabilidades e diferenças nos grupos sociais. A despeito de uma política criminal alternativa, o direito penal está longe de ser um instrumento efetivo a reduzir a incidência deste crime ou de prevenir, proteger e reconhecer as demandas das vítimas e dos outros segmentos atingidos. Propõe-se, assim, o aprimoramento das políticas públicas para que promovam níveis paritários de participação social entre os mais diversos...
Keywords: Direito penal; Direitos humanos; Prostituição; Tráfico humano - Aspectos jurídicos; Vítimas de tráfico humano; Sexo e direito